Quotations from Qur'anic Verses and Qira'at References in the Etymology of Words: The Example of Muhtaru's-Sihah - Bagis, Mehmet (Şırnak Univ, 2025)
In the texts written in the field of religious sciences, especially in Arabic language dictionaries, when a word is defined, it is demonstrated that the definition is sound, accurate and reliable by bringing an intellectual or Naqli evidence. In this way, the word acquires a generalized identity and is better understood. In this context, istishad with verses or referring to the differences of qiraat are among the primary references used to explain any word, concept or subject in religious texts. In essence, variations in recitation also fall within the scope of citing Qur'anic verses since authentic recitations and qira'at modes are considered part of the Qur'an due to their transmission through an uninterrupted chain of narration reaching the Prophet Muhammad. From the perspective of the Arabic language, it is observed that many dictionaries written over time have utilized Qur'anic verses as a method of citation, including references to different qira'at. This is because these dictionaries regard the Qur'an, the sacred book of the vast majority of Arabic speakers, as a primary source. Thus, the influence of the Qur'an on the meaning of some words and concepts used in dictionary terminology has been inevitable. Abu Bakr al-Razi (d. 666/1268) authored the lexicon Mukhtar al-Sihah in the field of Arabic linguistics by abridging al-Jawhari's (d. 400/1009) work al-Sihah/Taj al-Lugha wa-Sihah al-'Arabiyya. In addition to significant linguistic analyses conducted on words, Mukhtar al-Sihah contains numerous instances of Qur'anic citation (istishhad). Furthermore, references to qira'at are also occasionally employed in the lexicon to explain words, demonstrating the impact of recitational differences on meaning. The dictionary, arranged in alphabetical order according to the Arabic script, benefits from various disciplines of the Arabic language, such as morphology (sarf), syntax (nahw), rhetoric (balagha), and poetry, in explaining words. Almost every page features at least one Qur'anic citation. In the present study, which examines Mukhtar al-Sihah, an overview of the work, its author, and his scholarly contributions is provided first. Subsequently, the methodology of citation (istishhad) and reference to qira'at-methods used to substantiate claims or issues discussed in religious texts-are outlined in accordance with the subject matter. Within this framework, the Qur'anic citations in Mukhtar al-Sihah are analyzed in detail, while a separate section is dedicated to examining the role of qira'at in influencing meaning. Under the section on Qur'anic citation method and references to qira'at, examples are categorized based on the morphological structure of words, including nouns, verbs, and particles. Similarly, qira'at references are analyzed to illustrate how Mukhtar al-Sihah utilizes recitational variants as a means of citation. Although this abridged dictionary does not provide a systematic and comprehensive treatment of qira'at, it is evident that the work is not entirely devoid of references to them. At times, different recitational variants (qira'at wujuh) are mentioned concerning specific terms, along with the names of the reciters. Furthermore, in the context of recitational variants, the lexicon often includes the root forms of words, their morphological patterns, and whether they are singular or plural. Occasionally, the grammatical status of words and the meanings they acquire based on different recitational readings are also discussed. The presence of extensive linguistic analyses in dictionaries addressing Qur'anic citations and recitational differences also influences the interpretation of the relevant verses. Consequently, it has been observed that lexicons such as Mukhtar al-Sihah contribute to the field of tafsir (Qur'anic exegesis) and may even be considered among the sources of this discipline. Since Mukhtar al-Sihah systematically compiles words from the Qur'an, hadith, and other religious sources by selecting entries from al-Jawhari's al-Sihah, it has frequently been referenced in scholarly circles. However, upon examining the academic literature in the field of fundamental Islamic sciences, it becomes apparent that despite its reputation, relatively few studies have been conducted on this work. Therefore, this study, which aims to introduce the dictionary in broad terms and highlight the Qur'anic citations and recitational variations prominently featured in it, is expected to fill a significant gap in the field.
Keywords: Tafsir; Qur'anic Verse; Citation; Qira'at